ANALISIS PENDUGAAN BAHAYA KEGEMPAAN DI BATUAN DASAR UNTUK WILAYAH LAMPUNG MENGGUNAKAN METODE PSHA - Mhd Azri Pangaribuan; Syamsurijal Rasimeng; Karyanto Karyanto; Rudianto Rudianto (Engineering Faculty Universitas Lampung, 2019)
Analysis of seismic hazard estimation is one method for estimating the effect of earthquakes. The purpose of this study was to determine the maximum value of ground acceleration in bedrock or PGA values for the Lampung Province region. This analysis of seismic hazard estimation is carried out by a probabilistic seismic hazard analysis (PSHA) method. In the process of estimating the influence of earthquakes, the PSHA method principally uses 3 types of earthquake sources, namely the source of background earthquakes, subduction earthquakes (earthquake subduction) and fault earthquakes (faut). The calculation of the estimated seismic hazard value is carried out using the 2007 USGS PSHA program. The distribution of seismic hazard values for the Lampung Province region on bedrock with a 500-year return period or a 10% probability on the PGA condition (T = 0) is 0.1 g to 1, 3 g and a 2500 year return period or a probability of 2% in the PGA condition (T = 0) is 0.1 g to 1.3 g.